Front Cover: Dipolar Nanocars Based on a Porphyrin Backbone (Chem. Eur. J. 52/2020). Issue 52 (25th August 2020) - Nishino, Toshio; Martin, Colin J.; Takeuchi, Hiroki; Lim, Florence; Yasuhara, Kazuma; Gisbert, Yohan; Abid, Seifallah; Saffon‐Merceron, Nathalie; Kammerer, Claire; Rapenne, Gwénaël
Abstract : Control of molecular machines at the single molecular scale . The cover picture shows nanocars competing in the nanoworld, in anticipation of the 2nd Nanocar Race scheduled for 2021. These 2 nm‐long prototypes will be propelled thanks to their dipole under the action of an electric field induced by the tip of a Scanning Probe Microscope. This paper presents the design and synthesis of nine polar nanocars, incorporating strategic donor and acceptor combinations to fine‐tune the dipole. More information can be found in the Full Paper by G. Rapenne et al. on page 12010 .